2019
DOI: 10.1021/acs.macromol.8b02426
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-hexylthiophene) Grains Synthesized by Solvent-Free Oxidative Coupling Polymerization and Their Use as Light-Responsive Liquid Marble Stabilizer

Abstract: Solvent-free oxidative coupling polymerization of 3-hexylthiophene using FeCl3 oxidant was conducted to synthesize poly­(3-hexylthiophene) grains. Optical and scanning electron microscopy studies confirmed production of submillimeter-sized atypical grains with rough surfaces. Solubility test, Fourier transform infrared spectroscopy, and 1H nuclear magnetic resonance studies indicated the branching and cross-linking of the poly­(3-hexylthiophene). Elemental microanalysis and X-ray photoelectron spectroscopy stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 69 publications
(110 reference statements)
1
15
0
Order By: Relevance
“…After addition of the monomers to the FeCl 3 powder, an exothermic reaction occurred and temperatures increased to 350, 213, and 190 °C from 25 °C for PPy, PMPy, and PEPy systems, indicating progress of the polymerization. The yields after the purification were gravimetrically determined to be 74% (PPy), 56% (PMPy), and 63% (PEPy), which were similar to those reported previously for P3HT 30 and PEDOT 31 synthesized by solvent-free polymerization (67 and 52%). As comparison, the yields of PPy, PMPy, and PEPy synthesized by aqueous chemical oxidative polymerization were gravimetrically determined to be 89%, 47%, and 2%.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…After addition of the monomers to the FeCl 3 powder, an exothermic reaction occurred and temperatures increased to 350, 213, and 190 °C from 25 °C for PPy, PMPy, and PEPy systems, indicating progress of the polymerization. The yields after the purification were gravimetrically determined to be 74% (PPy), 56% (PMPy), and 63% (PEPy), which were similar to those reported previously for P3HT 30 and PEDOT 31 synthesized by solvent-free polymerization (67 and 52%). As comparison, the yields of PPy, PMPy, and PEPy synthesized by aqueous chemical oxidative polymerization were gravimetrically determined to be 89%, 47%, and 2%.…”
Section: Resultssupporting
confidence: 86%
“… 28 Huang et al synthesized polyaniline (PANI) by solvent-free mechanochemical oxidative polymerization of anilinium salts using ammonium persulfate. 29 Recently, we succeeded in syntheses of poly(3-hexylthiophene) (P3HT) 30 and poly(3,4-ethylenedioxythiophene) (PEDOT) 31 by solvent-free chemical oxidative polymerization in a one-step and one-pot manner and characterized the size and morphology of the products. PPy and its derivatives are promising and the most studied conjugated polymers; however and surprisingly, there has been no study on solvent-free chemical oxidative polymerization of Py and its derivatives by mechanical mixing to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…However, post‐functionalization exhibits poor conversion with many unreacted reaction sites. Aqueous polymerization of water‐soluble monomers is an alternate approach realized through Heck, [ 38,39 ] Sonogashira, [ 40,41 ] Suzuki, [ 42,43 ] and FeCl 3 ‐mediated oxidative [ 44,45 ] polymerizations. These reactions are successful when the active species tolerates the presence of water.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we confirmed that these conjugated polymer grains could adsorb to air‐water surface to stabilize LMs. Thanks to the coating with these conjugated polymer grains as an LM stabilizer, near‐infrared (NIR) light‐to‐heat photothermal properties could be introduced to the LM, and NIR laser irradiation could induce motion of the LM on a planar air‐water surface based on the light‐induced Marangoni propulsion 30,36,37 . Here, local irradiation of the LM with the NIR laser could generate a thermal gradient, and therefore surface tension gradient, around the LM, which could work as a driving force.…”
Section: Introductionmentioning
confidence: 99%